High-temperature-resistant and thermo-oxidative resin, synthesis method and preparation method of composite material of resin
By introducing silicon and boron elements into phenolic cyanate resin and phthalonitrile resin for copolymer modification, the problems of easy aging of resin at high temperature and high curing temperature are solved, the heat resistance and mechanical properties of composite materials are improved, and they are suitable for high temperature environments.
Patent Information
- Application Number
- CN202511032562.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-28
AI Technical Summary
Existing resin materials for radar radomes are prone to aging at high temperatures. Phthalonil resin has a high curing temperature and poor compatibility with phenolic cyanate resin, resulting in low mechanical properties, making it difficult to meet the requirements of high temperature resistance and thermo-oxidative aging resistance for radar radomes.
1,2-Diaminoo-carborane and silicic aromatic diamine bis(4-amino)dimethylsilane were used as curing agents to achieve copolymerization of phenolic cyanate resin and phthalonitrile resin, thereby reducing the curing temperature and introducing silicon and boron elements to improve the heat resistance and oxidation resistance of the resin.
This technology enables low-temperature curing of resins and improves their antioxidant properties at high temperatures, preventing phase separation and enhancing the heat resistance and mechanical properties of composite materials, making them suitable for high-temperature environments.
Smart Images

Figure CN120842565A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-temperature resistant and heat-oxidation resistant resin, its synthesis method, and the preparation method of its composite materials, belonging to the field of functional polymer materials technology. Background Technology
[0002] High-speed aircraft radar radomes require high wave transmission, load-bearing capacity, resistance to aerodynamic heating and high temperatures, and reusability. This necessitates that the electromagnetic functional materials used in radar radome manufacturing possess excellent comprehensive properties, including low dielectric constant, high temperature resistance, high strength, and resistance to thermo-oxidative aging. Cyanate ester resins, after curing, form a highly symmetrical cross-linked triazine ring structure, endowing them with excellent dielectric properties, high temperature resistance, low moisture absorption, and low shrinkage, making them considered "ideal resin matrices for radar radomes." Phenolic cyanate ester resins are among the most temperature-resistant cyanate ester resins, exhibiting excellent processability and suitability for manufacturing prepregs and composite materials; however, their insufficient resistance to thermo-oxidative aging limits their application. Phthalonil resins, since their successful development by the Keller team at the U.S. Naval Research Laboratory, have been widely used in aerospace, defense, and electronics fields due to their excellent heat resistance, thermo-oxidative resistance, mechanical properties, and dielectric properties. However, phthalonitrile resins require more than four days to gel at temperatures above 250°C, and their curing temperature is high, requiring a post-treatment process at 400°C. Therefore, catalysts are typically added to accelerate the curing and cross-linking process. Common catalysts include Lewis acids, organic amines, and organic phenols, which can catalyze the formation of various nitrogen-containing aromatic ring structures in phthalonitrile resins. Numerous studies have reported on the modification of phenolic cyanate ester resins with phthalonitrile resins, which can improve the heat resistance and thermo-oxidative aging resistance of phenolic cyanate ester resins; however, this requires increasing the curing temperature and sacrificing mechanical properties. The mechanical properties are lower than those of a two-resin combination, attributed to the incompatibility between the two resins and the presence of phase separation.
[0003] This paper addresses the urgent need in radar radome manufacturing for electromagnetic functional materials with excellent comprehensive properties, including low dielectric constant, high temperature resistance, high strength, and resistance to thermo-oxidative aging. It also addresses the problems associated with single-resin high-temperature resistant resin components, such as the insufficient thermo-oxidative aging resistance of phenolic cyanate resins and the high curing temperature and poor adhesion of phthalonitrile resins during film formation and application. Furthermore, simple blending and polymerization of two resins results in the presence of a phase interface in the composition, leading to lower mechanical properties compared to single-resin components. Summary of the Invention
[0004] Purpose of the invention: This patent proposes a silicon- and boron-containing phthalonitrile copolymer modified phenolic cyanate resin-based composite material and its preparation method. A composition of 1,2-diamino-o-carborane and silicon-containing aromatic diamine bis(4-amino)dimethylsilane is used as a curing agent for the cyanate resin and phthalonitrile resin. On the one hand, it acts as a crosslinking agent, achieving copolymerization of the cyanate resin and phthalonitrile resin and avoiding phase separation. On the other hand, it lowers the curing temperature of the cyanate resin and phthalonitrile resin. Furthermore, the introduction of silicon and boron elements into the resin components improves the heat resistance and thermo-oxidative aging resistance of the resin matrix and the composite material.
[0005] Technical solution: In one aspect, a high-temperature resistant and heat-oxidation resistant resin is provided, wherein the high-temperature resistant and heat-oxidation resistant resin is a phenolic cyanate ester resin modified by copolymerization of silicon and boron phthalonitrile. Wherein, the molecular formula is: .
[0006] Secondly, a method for synthesizing a high-temperature resistant and heat-oxidation resistant resin is provided, comprising: Step 1: Heat 100 parts of phenolic cyanate resin in a glass container, add 30 to 90 parts of phthalonitrile resin in stages, continue heating and stirring to obtain a mixed resin melt; Step 2: Cool down the temperature of the mixed resin melt, add 3 to 10 parts of the curing agent composition while stirring. After the curing agent composition is completely added, continue stirring to obtain a silicone and boron phthalonitrile copolymer modified phenolic cyanate resin, i.e., a mixed resin melt containing curing agent. The curing agent composition includes 1,2-diaminoo-carborane and silane-containing aromatic diamine bis(4-amino)dimethylsilane. Furthermore, in the first step, the heating temperature range of the phenolic cyanate ester resin is 120℃~130℃, the temperature range after heating is 170℃~180℃, and the stirring time range is 10min-20min.
[0007] Furthermore, in the second step, the temperature range after cooling is 140℃~150℃, and the stirring time ranges from 10min to 20min.
[0008] Furthermore, the mass ratio of the 1,2-diaminoo-carborane and the silane-containing aromatic diamine bis(4-amino)dimethylsilane composition is 7:3 to 5:5.
[0009] Thirdly, a method for preparing a high-temperature resistant and heat- and oxygen-resistant resin-based composite material is provided, characterized by comprising: A resin film is formed by coating the resin melt containing curing agent as described in claim 1 with a film at a temperature of 75℃ to 120℃ using a film coating machine; the resin film is then combined with a quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg is 30% to 45%; Prepreg layers are laid to obtain composite material laminate.
[0010] Furthermore, the number of layers is designed based on the thickness of the prepreg and the thickness of the laminate sample.
[0011] Furthermore, the composite material laminate is composed of quartz fiber fabric and silicon- and boron-containing phthalonitrile copolymer modified phenolic cyanate resin, and is cured and molded by oven or autoclave.
[0012] Beneficial effects: This invention proposes a silicon- and boron-containing phthalonitrile copolymer-modified phenolic cyanate ester resin-based composite material and its preparation method. A composition of 1,2-diaminoo-carborane and a silicon-containing aromatic diamine bis(4-amino)dimethylsilane is used as a curing agent for both the cyanate ester resin and the phthalonitrile resin. This composition acts as a crosslinking agent, enabling copolymerization of the cyanate ester resin and the phthalonitrile resin and preventing phase separation. It also lowers the curing temperature of both resins. Furthermore, the introduction of silicon and boron elements into the resin components enhances the heat resistance and thermo-oxidative aging resistance of the resin matrix and the composite material. The high-temperature resistant and thermo-oxidative resistant resin-based composite material component technology provided by this patent can offer theoretical guidance for other high-temperature resistant composite materials. The prepared phthalonitrile copolymer-modified phenolic cyanate ester resin-based composite material can be used as a skin for high-temperature resistant radar radome wave-transparent composite materials, providing a material basis for the upgrading of aerospace equipment. Attached Figure Description
[0013] Figure 1 This is a molecular structure diagram of phenolic cyanate resin.
[0014] Figure 2 The molecular structure diagrams are of bisphenol A and bisphenol AF phthalonitrile resins.
[0015] Figure 3 The diagram shows the molecular structure of 1,2-diaminoo-carborane.
[0016] Figure 4 It has the molecular structure of bis(4-amino)dimethylsilane containing silicon aromatic diamine. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other, and the various embodiments can be referenced and cited in each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0019] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0020] The preparation of the silicon- and boron-containing phthalonitrile copolymer modified phenolic cyanate resin-based composite material of the present invention includes the following four steps; Step 1: Place 100 parts of phenolic cyanate resin (molecular structure as shown) in a glass container. Figure 1 (As shown) Heat to 120℃~130℃, and add 30~90 parts of phthalonitrile resin (bisphenol A type, bisphenol AF type phthalonitrile resin, molecular structure as shown) in steps. Figure 2 As shown in the figure, the temperature is raised to 170℃~180℃ and stirred continuously for 10min-20min to obtain a mixed resin melt; Step 2: Lower the melt temperature of the mixed resin to 140℃~150℃, and add 1,2-diaminoo-carborane (molecular structure as shown in the image). Figure 3 (as shown) and silicic aromatic diamine bis(4-amino)dimethylsilane (molecular structure as shown) Figure 4 (As shown) 3 to 10 parts of the composition, wherein the mass ratio of 1,2-diaminoo-carborane and silicic aromatic diamine bis(4-amino)dimethylsilane is 7:3 to 5:5; the curing agent composition is added while stirring, and after it is completely added, stirring is continued for 10 min to 20 min to obtain a mixed resin melt containing the curing agent; Step 3: Using a film coating machine, the resin melt containing curing agent is coated into a resin film at 75℃~120℃; the resin film is then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg is 30%~45%; Step 4: The prepreg is laid layer by layer. The number of layers can be designed according to the thickness of the prepreg and the thickness of the laminate sample. It is cured in an oven or autoclave to obtain a high-temperature resistant and heat- and oxygen-resistant composite material laminate.
[0021] Example 1 In a glass container, 100 parts of phenolic cyanate resin (molecular structure shown in the figure below) were heated to 120°C. Then, 50 parts of phthalonitrile resin (bisphenol A and bisphenol AF phthalonitrile resins in a 50:50 mass ratio) were added stepwise. The temperature was raised to 170°C, and the mixture was stirred continuously for 20 minutes to obtain a mixed resin melt. The temperature of the mixed resin melt was then lowered to 140°C, and 6 parts of a composition of 1,2-diamino-o-carborane and silicone-containing aromatic diamine bis(4-amino)dimethylsilane were added. The aromatic diamine bis(4-amino)dimethylsilane composition was prepared in a mass ratio of 5:5. The curing agent composition was added while stirring, and after complete addition, stirring was continued for 20 minutes to obtain a mixed resin melt containing the curing agent. The mixed resin melt containing the curing agent was coated into a resin film at 120°C using a film coating machine. The resin film was then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg was 40%. The prepreg was layered and cured in an oven or autoclave. The curing regime was 180°C±5°C×2h±0.5h + 250°C±5°C×2h±0.5h + 280°C±5°C×3h±0.5h to obtain a high-temperature resistant and heat-oxidation resistant composite laminate.
[0022] The dielectric (waveguide method), heat resistance (DMA method, ASTM D 7028-07(2024)), tensile (ASTM D3039), and shear (ASTM D3039) mechanical properties of the composite laminate were characterized. The mechanical properties of the composite material after 100 h of thermo-oxidative aging at 350℃ were also characterized, and the mechanical property retention rate was calculated. The test results are summarized in the table below.
[0023] Example 2 In a glass container, 100 parts of phenolic cyanate resin (molecular structure shown in the figure below) were heated to 120°C. Then, 90 parts of phthalonitrile resin (bisphenol A and bisphenol AF type phthalonitrile resins in a 50:50 mass ratio) were added stepwise. The temperature was raised to 170°C, and the mixture was stirred continuously for 20 minutes to obtain a mixed resin melt. The temperature of the mixed resin melt was then lowered to 140°C, and 10 parts of a composition of 1,2-diamino-o-carborane and silanized aromatic diamine bis(4-amino)dimethylsilane were added. The mass ratio of the silanol diamine bis(4-amino)dimethylsilane composition is 7:3. The curing agent composition is added while stirring, and after complete addition, stirring is continued for 20 minutes to obtain a mixed resin melt containing the curing agent. The mixed resin melt containing the curing agent is coated into a resin film at 120℃ using a film coating machine. The resin film is then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg is 40%. The prepreg is layered and cured in an oven or autoclave. The curing regime is 180℃±5℃×2h±0.5h +250℃±5℃×2h±0.5h +280℃±5℃×3h±0.5h to obtain a high-temperature resistant and heat-oxidation resistant composite laminate.
[0024] The test results of the composite material properties are summarized in the table below.
[0025] Example 3 In a glass container, 100 parts of phenolic cyanate resin (molecular structure shown in the figure below) were heated to 120°C. Then, 30 parts of phthalonitrile resin (bisphenol A and bisphenol AF type phthalonitrile resins in a 50:50 mass ratio) were added stepwise. The temperature was raised to 170°C, and the mixture was stirred continuously for 20 minutes to obtain a mixed resin melt. The temperature of the mixed resin melt was then lowered to 140°C, and 10 parts of a composition of 1,2-diaminoo-carborane and silanized aromatic diamine bis(4-amino)dimethylsilane were added. The mass ratio of the silanol diamine bis(4-amino)dimethylsilane composition is 5:5. The curing agent composition is added while stirring, and after complete addition, stirring is continued for 20 minutes to obtain a mixed resin melt containing the curing agent. The mixed resin melt containing the curing agent is coated into a resin film at 120℃ using a film coating machine. The resin film is then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg is 40%. The prepreg is layered and cured in an oven or autoclave. The curing regime is 180℃±5℃×2h±0.5h +250℃±5℃×2h±0.5h +280℃±5℃×3h±0.5h to obtain a high-temperature resistant and heat-oxidation resistant composite laminate.
[0026] The test results of the composite material properties are summarized in the table below.
[0027] Compare with Example 1 In a glass container, 100 parts of phenolic cyanate resin (molecular structure shown in the figure below) were heated to 120°C. Then, 30 parts of phthalonitrile resin (bisphenol A and bisphenol AF phthalonitrile resins in a 50:50 mass ratio) were added stepwise. The temperature was raised to 170°C, and the mixture was stirred continuously for 20 minutes to obtain a mixed resin melt. The composition of 1,2-diamino-o-carborane and silicic aromatic diamine bis(4-amino)dimethylsilane was not added. Using a film coating machine, the mixed resin melt containing the curing agent was coated into a resin film at 120°C. The resin film was then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg was 40%. The prepreg was layered and cured in an oven or autoclave. The curing regime was 180°C±5°C×2h±0.5h + 250°C±5°C×2h±0.5h. +280℃±5℃×3h±0.5h, a high-temperature resistant and heat-oxidation resistant composite material laminate is obtained.
[0028] The test results of the composite material properties are summarized in the table below.
[0029] Compare with Example 2 100 parts of phenolic cyanate resin (molecular structure shown in the figure below) were heated to 120°C in a glass container without adding phthalonitrile resin. The resin melt temperature was lowered to 80°C, and 3 parts of a composition of 1,2-diamino-o-carborane and silicic aromatic diamine bis(4-amino)dimethylsilane were added, wherein the mass ratio of 1,2-diamino-o-carborane to silicic aromatic diamine bis(4-amino)dimethylsilane was 5:5. The curing agent composition was added while stirring, and after complete addition, stirring was continued for 20 minutes to obtain a mixed resin melt containing the curing agent. The mixed resin melt containing the curing agent was coated into a resin film at 120°C using a film coating machine. The resin film was then laminated with quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg was 40%. The prepreg was layered and cured in an oven or autoclave at a curing regime of 180°C ± 5°C × 2h ± 0.5h. +250℃±5℃×2h±0.5h +280℃±5℃×3h±0.5h, a high-temperature resistant and heat-oxidation resistant composite material laminate is obtained.
[0030] The test results of the composite material properties are summarized in Table 1.
[0031] Table 1
Claims
1. A high-temperature resistant and heat-oxidation resistant resin, characterized in that, The high-temperature resistant and heat-oxidation resistant resin is a phenolic cyanate ester resin modified by copolymerization of silicon and boron phthalonitrile; Wherein, the molecular formula is: 。 2. A method for synthesizing a high-temperature resistant and heat-oxidation resistant resin, characterized in that, include: Step 1: Heat 100 parts of phenolic cyanate resin in a glass container, add 30 to 90 parts of phthalonitrile resin in stages, continue heating and stirring to obtain a mixed resin melt; Step 2: Cool down the temperature of the mixed resin melt, add 3 to 10 parts of the curing agent composition while stirring. After the curing agent composition is completely added, continue stirring to obtain a silicone and boron phthalonitrile copolymer modified phenolic cyanate resin, i.e., a mixed resin melt containing curing agent. The curing agent composition includes 1,2-diaminoo-carborane and silane-containing aromatic diamine bis(4-amino)dimethylsilane.
3. The method according to claim 2, characterized in that, In the first step, the heating temperature range of the phenolic cyanate resin is 120℃~130℃, the temperature range after heating is 170℃~180℃, and the stirring time range is 10min-20min.
4. The method according to claim 3, characterized in that, In the second step, the temperature range after cooling is 140℃~150℃, and the stirring time ranges from 10min to 20min.
5. The method according to claim 2, characterized in that, The mass ratio of the composition of 1,2-diaminoo-carborane and silicic aromatic diamine bis(4-amino)dimethylsilane is 7:3 to 5:
5.
6. A method for preparing a high-temperature resistant and heat-oxidation resistant resin-based composite material, characterized in that, include: A resin film is formed by coating the resin melt containing curing agent as described in claim 1 with a film at a temperature of 75℃ to 120℃ using a film coating machine; the resin film is then combined with a quartz fiber fabric to obtain a prepreg coated with resin film on both sides, wherein the resin content of the prepreg is 30% to 45%; Prepreg layers are laid to obtain composite material laminate.
7. The method according to claim 6, characterized in that, The number of layers is designed based on the thickness of the prepreg and the thickness of the laminate sample.
8. The method according to claim 7, characterized in that, The composite material laminate is composed of quartz fiber fabric and silicon- and boron-containing phthalonitrile copolymer modified phenolic cyanate resin, and is cured in an oven or autoclave.
Citation Information
Cited By
High-heat-resistance cyanate ester resin system capable of being cured at low temperature and preparation method
CN121673825A